State-of-charge estimation method for lithium-ion batteries based on competitive SIR model - Xu, Guimin (Frontiers in Energy Research, 2022)
In order to meet the needs of life and production and ensure the battery is stable when using the battery, a scheme for reckoning the state of charge of lithium-ion batteries derived from the competitive SIR model is proposed. During the charging process of the battery, the electrolyte and the diaphragm reach the negative electrode of the battery, and the electrolyte escapes from the graphite of the negative electrode to the positive electrode in the case of discharge. The analysis shows that the SIR model belongs to the internal information evolution process, which can infect the surrounding data and evaluate the state of charge better. Through experiments, it is substantiated that the scheme is able to better estimate the state of lithium-ion batteries, the error value is 0.0189, the accuracy is good, and the battery usage can be predicted in time.